Answer:
a. f(x)^(-1)=x/3
b. f(x)^(-1)=log_10x/log_10〖1/2〗
c. g(x)^(-1)=e^x+7
d. f(x)^(-1)=5^x-2
e. f(x)^(-1)=(x-3)/1.08
f. f(x)^(-1)=((2^x-4)/3)^2
g. h(x)^(-1)=x/(5-5x)
h. f(x)^(-1)=x+3
Explanation:
To understand how to find the inverse function you must solve the equation for x and then replace x by the definition of the inverse f(x)-1. Then the explanation of each exercise goes as follows:
a. f(x)=3x
f(x)/3=x
f(x)^(-1)=x/3
b.f(x)=(1/2)^(x )
Considering that log_b(a)=c and log_b(a)=log_c(a)/log_c(b)
log_(1/2) f(x)=log_(1/2)((1/2)^x )
log_(1/2) f(x)=x
f(x)^(-1)=log_(1/2) (x)=log_10(x)/log_10(1/2)
c. g(x)=ln(x-7)
Considering that ln(e^x )=x
e^g(x) =e^ln(x-7)
e^g(x) =(x-7)
x=e^g(x) +7
g(x)^(-1)=e^x+7
d. h(x)=log_3(x+2)/log_3(5)
log_3(x+2)/log_3(5) =log_5(x+2)
h(x)=log_5(x+2)
5^h(x) =x+2
h(x)^(-1)=5^x-2
e. f(x)=3*1.8*0.2*x+3
f(x)=3*1.8*0.2*x+3
f(x)^(-1)=(x-3)/1.08
f. f(x)=log_2(3√x-4)
2^f(x) =2^log_2(3√x-4)
2^f(x) -4=3√x
((2^f(x) -4)/3)^2=√x^2
f(x)^(-1)=((2^x-4)/3)^2
g. h(x)=5x/(5x+1)
(5x+1)h(x)=5x
h(x)=5x(1-h(x))
x=h(x)/5(1-h(x))
h(x)^(-1)=x/(5(1-x))
h. f(x)=2-x+1=3-x
f(x)^(-1)=3+x